Single-Level Cervical Arthroplasty with a Keel-less Prosthesis: Results in a Series of 35 Patients Operated on for Soft Disk Herniation with a Minimum of 3 Years of Follow-Up - Stifano, Vito; Stati, Giovanni; Giacobbo Scavo, Carlo; Carpineta, Ettore; Cacciotti, Guglielmo; Roperto, Raffaelino; Sufianov, Albert; Mastronardi, Luciano (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Cervical arthroplasty with artificial cervical disks has gained popularity as an alternative to anterior discectomy and fusion. The main advantages of disk arthroplasty include maintenance of the range of movement, restitution of disk height and spinal alignment, and reduction of adjacent segment degeneration (ASD). In this article, we aimed to assess the outcomes of the use of a keel-less prosthesis.Material and Methods We included all the patients who underwent single-level cervical arthroplasties with the Discocerv Cervidisc Evolution for “soft” disk herniation. Clinical assessment included Neck Disability Index (NDI) and visual analog scale (VAS) for neck and arm pain. Radiologic studies investigated the occurrence of ASD and system failure or subsidence. The reoperation rate was also recorded.Results The study included 35 patients (14 men and 21 women; mean age: 42.5 years; mean follow-up: 57.8 months). There was a significant decrease in VAS neck and VAS arm scores, which went from 7.2 and 6.9 preoperatively to 2.2 and 1.7 postoperatively, 2.2 and 1.6 at 6 months, 2.0 and 1.8 at 1 year, and 2.1 and 1.3 at the last follow-up, respectively. The mean NDI score was 58.0 preoperatively, 19.4 postoperatively, 17.0 at 6 months, 16.1 at 1 year, and 16.2 at the last follow-up. Radiologic studies revealed a preserved range of motion in 33 of 35 patients. No ASD occurred and no reoperation was required.Conclusions Cervical disk arthroplasty with a keel-less prosthesis can be a safe and effective alternative to fusion for degenerative disk disease in selected patients, with a possible reduction of ASD.
Keywords: Discocerv; cervical arthroplasty; disk prosthesis; disk replacement; cervical herniation